PRINSIP-PRINSIP PENGEMBANGAN KURIKULUM - Bradley Setiyadi; Revyta Revyta; Ayunda Fadhilah (Universitas Muhammadiyah Purwokerto, 2020)
ABSTRACT The curriculum is the core of the education process in schools. The implementation of the curriculum directly influences the educational outcomes. The curriculum really determines the process and results of an education system. The curriculum is a description of the material presented in learning, is also a very important component in an education system, the curriculum is a tool to achieve educational goals and at the same time as a guide in the implementation of teaching at all types and levels of education. Curriculum development is a process that plans, produces a better tool based on the results of an assessment of the curriculum that has been in effect, so that it can provide good teaching and learning conditions. In other words curriculum development is an activity to produce a new curriculum through the steps of curriculum preparation based on the results of the assessment conducted over a certain period of time. Curriculum principles can also be regarded as rules that animate curriculum development. This principle has the aim that the curriculum is designed or produced in accordance with the demands of all parties, namely students, parents, community and nation. In general, curriculum experts view curriculum development activities as a continuous process, a cycle that involves several curricula, namely components, objectives, materials, activities and evaluations. This paper uses the method of theoretical study of the principles of curriculum development. The theories put forward in this paper are understanding the curriculum and its developers, plus theories about the sources and principles of curriculum development, learning and evaluation of curriculum development. Keywords: curriculum concept, curriculum development, curriculum principles